Empowering Futures: a Business Model Canvas (BMC) Approach to Enhancing Productivity in Retirement for KMS PT Indofood CBP Sukses Makmur Tbk. Cooperative Members - Rimadias, Santi (Asian Journal of Community Services, 2024)
Self-development can help employees to stay productive in retirement. One of the training that can help develop employees to prepare for retirement is Business Model Canvas (BMC) training. The purpose of the implementation of community service is BMC training to prepare for the retirement of KMS Cooperative members of PT Indofood CBP Sukses Makmur Tbk. The method used is in the form of training. The success indicator in the implementation of this BMC training program is that 80% of trainees can compile a planned and measurable business plan. The training results show that almost 100% of trainees can develop a planned and measurable business plan that is expected to support them to remain active and productive after retirement.